Fatal Klebsiella pneumoniae meningitis in a patient with diabetes mellitus and Hansen's disease - Vani Gopal; T Mangaiyarkarasi; R Gopal (Wolters Kluwer Medknow Publications, 2014)
Klebsiella is a Gram-negative bacterium that causes different types of health care-associated infections including pneumonia, bloodstream infections, surgical site infections and meningitis. We report here a case of Klebsiella pneumoniae meningitis in a patient with diabetes mellitus and Hansen's disease. A middle-aged man with a known case of diabetes mellitus and Hansen's disease presented with the complaints of blurred vision in the left eye and the patient was found to have cataract. Patient was operated for cataract and Intraocular lens implanted. Patient developed headache and vomiting on the 4 th post-operative day. Lumbar puncture was carried out and gram stain of cerebrospinal fluid showed Gram-negative bacilli in the direct smear and culture yielded a heavy growth of K. pneumoniae. The patient was treated with antimicrobials according to the susceptibility pattern. He initially showed improvement but later on developed altered sensorium and hypotension. Patient succumbed to infection in spite of all medical attention.